Prevention of impaired quality of life in young patients with gastroesophageal reflux disease and autoimmune thyroiditis - Pasiieshvili, T.; Kovalyova, Olga (Андижанский государственный медицинский институт, 2019)
Prevention of impaired quality of life in young patients with gastroesophageal reflux disease and autoimmune thyroiditis
Keywords: quality of life; prevention of impaired quality; young patient; gastroesophageal reflux disease; autoimmune thyroiditis